The influence of the political-socialmacrossystem structure on the balance of the work environment and worker's mental health - Almeida, Victor Hugo de [UNESP]; Guimaraes Marcondes Machado, Caio Mendes [UNESP] (Univ Estado Rio Janeiro, 2023)
The current Brazilian political-social scenario, driven, predominantly, by the Neoliberal economic system, triggered several effects in the whole society. Among these effects, one can point out its remarkable interference in a basic structure of all its functioning: work. The work environment tends to be governed by current economic concepts and socio-political structures. Concomitantly, nowadays, the phenomenon of mental illness is also perceived, which increasingly plagues the working class, often caused by working conditions. In this way, the present study seeks to analyze the current conception of the work environment, from the Labor-environmental Perspective Theory - as a theoretical matrix - and the current legislation, to, from it, identify aspects of the labor and social context. policy related to the triggering of mental and behavioral disorders listed in the ICD-10 (F00-F99). For that, it was adopted, as a method of procedure, the survey through the technique of bibliographic research in published materials; and, as a method of approach, the deductive. It was concluded that the socio-political aspects influence the balance of the work environment and the mental health of the worker, given their particularities and their central objectives of capital control and, consequently, of the structures of power and the means of production.
Keywords: socio-political context; Labor law; occupational disease; work environment; mental and behavioral disorders